KERAGAAN PEDAGANG MAKANAN JAJANAN OLAHAN DI KAMPUS UNIVERSITAS LAMPUNG - Ningsih, Dwi Surya; Indriani, Yaktiworo; Suryani, Ani (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2018)
This study aims to determine the vendors performance and street foods at the University of Lampung (Unila) Campus, analyze the capital cost, revenue and profits of street food vendors at Unila Campus. The research is carried out at Unila Campus on purpose, which is in the canteen of Agricultural Faculty, Engineering Faculty, and Library as well as around the Unila food ball field by survey method. The data was collected from January to February 2017. The subjects of this study were heavy and light snack food vendors who have been selling food at least a year. Research data was analyzed descriptively. The results showed that there were 22 types of heavy snack foods and 10 types of light snacks and drinks. The initial capital expenditure at the street food vendors derived from their savings were ranging from Rp70,000.00 to Rp7,000,000.00. The revenue of street food vendors ranged from Rp5,000,000.00 to Rp92,000,000.00 per month. The average profit analysis results showed that vendors benefit from self processing street foods in average was Rp6,288,439.00 per the month for locations in Unila ball field; Rp12,471,155.00 at the Faculty of Agriculture; Rp12,868,096.00 at the Unila library, and Rp7,110,383.00 at around the Faculty of Engineering. Key words: profit analysis, street food vendors